Os benefícios de projetos de automatização por robôs em empresas de manufatura - Souza, Renan Rubim de Castro (2024)
Considering the advances in digital transformations and Industry 4.0, organizations are facing accelerated technological developments that positively contribute to these projects. Manufacturing companies, in turn, are seeking robotic automation to improve their competitiveness, yet they are not fully identifying the real benefits of this technology. An integrated approach, such as Benefits Management proposed by Ward and Daniel (2012), has helped in understanding how companies can gain technological advantages by adopting the "Benefits Dependency Network" model, providing a more comprehensive analysis of the benefits of technology investments. Thus, the objective of this dissertation was defined as proposing a Benefits Dependency Network for robotic automation projects in manufacturing companies, aiming to answer the following research question: How can the benefits of robotic automation projects in manufacturing companies be identified and structured? Based on this objective, the following specific goals were presented: (a) Identify the main organizational elements that guide the adoption of robotic automation projects; (b) Describe the organizational objectives that drive the adoption of robotic automation projects; (c) Identify the benefits resulting from the adoption of robotic automation projects; (d) Understand how these robotics technologies are operationalized; (e) Understand the changes required to achieve the desired benefits; and (f) Investigate the transformations in the organizational environment resulting from these emerging technologies. This research conducted a Systematic Literature Review and followed a qualitative and exploratory approach, through the analysis of four case studies in different manufacturing organizations (consumer goods, electronics, healthcare equipment, and automotive) that implemented robotic automation projects. Twenty-two interviews were conducted with professionals from these companies, complemented by direct observation and document analysis. This dissertation identified benefits of robotic automation in industry, including human and sustainable advancements, focusing on well-being and environmental sustainability, and productivity improvements, with enhancements in quality, precision, and the development of new products. As a contribution, a framework was presented for the identification and structuring of these benefits in robotic automation projects in manufacturing. Thus, future research is recommended to investigate the entire Benefits Management in robotic automation projects.